Dodecenyl succinic anhydride starch nanocrystal, preparation method for preparing active film liquid by using starch nanocrystal and fruit preservation application of starch nanocrystal
Stable thymol Pickering emulsion was prepared by treating dodecenyl succinic anhydride esterified starch nanocrystals with plasma jet, which solved the problem of high volatility of thymol during fruit preservation and achieved an environmentally friendly fruit preservation effect.
Patent Information
- Application Number
- CN202411584213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
AI Technical Summary
In existing technologies, thymol is highly volatile during fruit preservation, resulting in high concentrations in the storage environment and causing phytotoxicity. Furthermore, food packaging plastics cause environmental pollution, and there is a lack of environmentally friendly and stable methods for fruit preservation.
Dodecenyl succinic anhydride (DDSA) esterified starch nanocrystals (SNC) were prepared by synergistic treatment with atmospheric pressure plasma jet (APPJ) to stabilize thymol Pickering emulsion and distribute it uniformly in starch film liquid to form an antibacterial and antioxidant active film.
It slows down the release rate of thymol, extends the storage time of fruits, reduces the volatility of thymol, improves the preservation effect of fruits, and reduces environmental pollution.
Smart Images

Figure CN119264283A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of succinic anhydride starch nanocrystal preparation technology, relates to a preparation method of dodecenyl succinic anhydride starch nanocrystal, and also relates to use of dodecenyl succinic anhydride starch nanocrystal for preparing active film liquid and use of dodecenyl succinic anhydride starch nanocrystal for fruit preservation. Background Art
[0002] During the growth and storage of early pears, apples and other fruits, they are easily infected by fungi such as cross-linked spores and Penicillium. Food packaging is one of the ways to prevent fungal infection and reproduction, but plastic packaging has caused serious environmental pollution, so there is an urgent need to find alternatives to food packaging. Thymol is a common substance in many plant essential oils such as thyme and oregano essential oils. It has antibacterial and antioxidant effects and can be used to inhibit fruit oxidation and microbial growth during fruit preservation. However, thymol is highly hydrophobic and easily volatile. A large amount of volatilization in a short period of time will lead to a high concentration of thymol in the storage environment, causing phytotoxicity to the preserved fruits.
[0003] Pickering emulsion is a stable emulsion system stabilized by solid particles instead of surfactants. Solid particles are irreversibly adsorbed on the oil-water interface of the emulsion, which can effectively prevent the aggregation of emulsion droplets and give Pickering emulsion better physical stability. However, their adsorption mechanisms are different. Most solid particles are not amphiphilic. They mainly rely on the partial wettability of water and oil on the surface of solid particles to stabilize the solid particles in the emulsion. When the solid particles are equally wetted by the oil phase and the water phase, the desorption energy is the highest and the emulsion stability is the strongest. Starch nanocrystals can be obtained by removing the amorphous part of onion-shaped starch granules through physical treatment or acid hydrolysis. They are nano-sheet-shaped crystals with certain resistance to acid. Starch nanocrystals have good rigidity and are suitable for stabilizing Pickering emulsions. In particular, thymol Pickering emulsions stabilized by amphiphilic esterified starch nanocrystals can make hydrophobic volatile active substances have excellent stability, reduce the loss of thymol during the formation of active film, and limit its sudden release in the active film.
[0004] The present invention firstly uses atmospheric pressure plasma (APPJ) to co-treat the reaction of dodecanedioyl succinic anhydride (DDSA) esterified starch nanocrystals (SNC), thereby increasing the degree of substitution of DDSA-SNC, enhancing its hydrophobic properties, and making it amphiphilic. The prepared DDSA-SNC can be used to stabilize thymol Pickering emulsion and evenly distribute it in the starch film liquid. After the film liquid is dried, it has a fixing effect on thymol, slows down the release rate of thymol, and prolongs the release time. The method effectively controls the release process of thymol and prolongs the storage time of early crisp pears. After thymol is encapsulated with Pickering emulsion, it is evenly distributed in the coating liquid. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a dodecenylsuccinic anhydride starch nanocrystal, a preparation method of an active film liquid using the starch nanocrystal, and its application in fruit preservation, so as to solve the problems existing in the prior art.
[0007] The scheme implemented by the present invention is: a method for preparing dodecenyl succinic anhydride starch nanocrystals, which comprises: after the starch nanocrystals are prepared into a suspension, a dodecenyl succinic anhydride (DDSA) ethanol solution is added to carry out an esterification reaction, and during the esterification reaction, an atmospheric pressure plasma jet (APPJ) treatment is simultaneously carried out. After the reaction is completed, the starch nanocrystals are centrifuged and washed, and then freeze-dried to obtain dodecenyl succinic anhydride starch nanocrystals.
[0008] A method for preparing dodecenyl succinic anhydride starch nanocrystals is as follows: 1g of prepared SNC is added to 30mL of 50% ethanol solution, and ultrasonically vibrates in a water bath for 30min to obtain a SNC (starch nanocrystal) suspension, and 1g of DDSA is fixed to volume with anhydrous ethanol in a 5mL volumetric flask to prepare a DDSA-ethanol solution with a concentration of 0.2g / mL. 400μL of DDSA-ethanol solution is added dropwise to the SNC suspension, and the esterification reaction is carried out at 35°C and 200r / min with stirring. APPJ treatment is started 24min before the end of the reaction. After the reaction, centrifugation is performed and washed with 70% ethanol and anhydrous ethanol for 3 times respectively, and freeze-dried for use.
[0009] Furthermore, the APPJ processing power is 300w, the air flow is 20mL / s, the entire esterification reaction time is 3h, of which the APPJ processing time is 24min.
[0010] Furthermore, during the above reaction, 0.1 mol / L NaOH was used to adjust the pH of the reaction solution to maintain the pH of the reaction solution between 8.5 and 9.5, and after the reaction, 0.1 mol / L HCl was used to adjust the pH to 6.8 to terminate the reaction.
[0011] Furthermore, the esterification reaction was treated with APPJ 24 minutes before the end of the reaction.
[0012] A method for preparing an active film liquid comprises the following steps: blending a DDSA-SNC stabilized Pickering emulsion with a potato starch film-forming matrix to obtain the active film liquid.
[0013] Furthermore, the specific preparation method of the above-mentioned DDSA-SNC stabilized Pickering emulsion is: using dodecenylsuccinic acid starch nanocrystals as a stabilizer to prepare a thymol mixed solution (THY), using a high-speed homogenizer to mix 5 mL of distilled water and 5 mL of thymol solution at room temperature at a speed of 10,000 rpm, and homogenizing 3 times, each time for 1 min, wherein the mass ratio of thymol to anhydrous ethanol is 1:2; before homogenization, 0.25 g of dodecenylsuccinic acid starch nanocrystals is added to the thymol mixed solution THY, and the Pickering emulsion is prepared after homogenization.
[0014] Furthermore, the preparation method of the above-mentioned potato starch film liquid (PS) is as follows: 100g of potato starch is mixed with 2mL of glycerol and 100mL of distilled water, and the mixture is placed in a water bath at 90°C for 30min, and continuously stirred (200r / min) until completely gelatinized, and then cooled for use, and Pickering emulsion is added to the potato starch film liquid and stirred evenly to obtain a PS / PE film liquid.
[0015] Furthermore, 4% Pickering emulsion (E-24 stabilized thymol emulsion) was added to the potato starch film liquid and stirred evenly to obtain a film-forming liquid.
[0016] The prepared active film-forming liquid is applied on the surface of fruits for preservation.
[0017] The effects of the present invention are as follows: (1) DDSA esterification and APPJ synergistic treatment can increase the degree of substitution of DDSA on SNC, reduce the critical aggregation concentration of DDSA-SNC, and increase WCA (water contact angle). This is mainly due to the high-energy substances generated during the plasma generation process bombarding the surface of SNC, resulting in the cleavage of the glycosidic bonds in the molecular structure of the glucose unit, especially the COC of the α-1,6 glycosidic bonds, which leads to a decrease in the branching degree of SNC and depolymerization, thereby increasing the -OH content, exposing more reaction sites, and increasing the degree of substitution and substitution efficiency of DDSA; SEM results show that etching marks appear on the surface of the particles after APPJ treatment, and the cleavage of the glycosidic bonds destroys the crystallization area, resulting in a decrease in the relative crystallinity of DDSA-SNC, and a decrease in the peak temperature and thermal enthalpy of DSC degradation. Large particles of DDSA-SNC are depolymerized after synergistic treatment, and the volume is reduced, resulting in a decrease in particle size and PDI. During the APPJ treatment, oxygen in the air ionizes and oxidizes the DDSA-SNC particles, reducing the potential. At the same time, after the degree of substitution increases, the number of negatively charged -COO- groups on the particle surface increases, which also leads to a decrease in the negative potential of the particles. This indicates that DDSA esterification and APPJ synergistic treatment can improve the degree of substitution of DDSA-SNC, solve the problem of low substitution efficiency of DDSA for SNC, and reduce the particle size and increase the absolute potential, making DDSA-SNC more suitable as a nanoparticle for stabilizing Pickering emulsions. This is a green and simple improvement method.
[0018] (2) A feasible antioxidant and antibacterial coating was obtained by preparing Pickering emulsion using DDSA-SNC and mixing it in a starch-based film. The Pickering emulsion stabilized by DDSA-SNC was blended with a potato starch film-forming matrix to prepare an active film with antibacterial and antioxidant functions by a casting method. The results showed that during the drying process of the active coating liquid PS-THY, thymol gradually migrated to the surface of the starch film as the water evaporated. However, in the PS-PE coating liquid, the Pickering emulsion and the free starch chains in the starch gelatinized liquid crossed each other and were embedded in the network structure of the starch film. The Pickering emulsion and the film matrix formed a stable structure, and most of the thymol was retained in the starch film after film formation. Due to the uniform distribution of thymol Pickering emulsion in the film-forming matrix, dense and uniform pores were formed in the dried starch film, making the film have the characteristics of sustained release. In addition, the application of the active coating liquid had a positive effect on the early pear, which was confirmed by the postharvest physiological quality, including lower weight loss, higher hardness and lower respiration rate. In summary, Pickering emulsion can be used as an effective method to carry active substances in the process of film preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 are Fourier transform infrared spectra, where (a) is the Fourier transform infrared spectrum of starch nanoparticles, and (b) is the Fourier transform infrared deconvolution spectrum; Figure 2 is the H NMR spectrum; Figure 3 is the XRD diffraction pattern; Figure 4 It is the DSC differential scanning thermodynamic diagram; Figure 5 This is the SEM result diagram; Figure 6 is the average particle size and potential diagram of nanoparticles; Figure 7 is the particle size distribution diagram of nanoparticles; Figure 8 is the average particle size diagram of Pickering emulsion; Fig. 9 is the particle size distribution diagram of Pickering emulsion; Fig.10 is the ζ-potential diagram of the Pickering emulsion; Fig.11 It is an emulsion microscope and macroscopic photograph; Fig.12 is the emulsification index curve of the emulsion at different storage times; Fig.13 This is a microscope macroscopic photograph of thymol / starch composite membrane solution; Fig.14 are the particle size distribution curves of the three membrane solutions; Fig.15 is the curve of viscosity changing with shear rate; Fig.16 is the curve of the change of the storage loss modulus G of the membrane liquid with the angular frequency; Fig.17 is the thymol encapsulation rate curve; Fig.18 is the change of thymol content and xylitol addition amount; Fig.19 This is the structural relationship diagram between E-24, thymol and starch membrane simulated by molecular dynamics; Fig. 20 This is the interaction diagram of van der Waals force and Coulomb force in PS / PE; Fig.21 This is the interaction diagram of van der Waals force and Coulomb force in PS / CE; Fig. 22 is the interaction diagram of the hydrogen bonds between ps / pe and ps / ce; Fig.23 MSD diagram of ps / pe and ps / ce; Fig.24 These are photos of the preservation and freshness of Zaosu pears after film coating; Fig.25 is the color difference value Δa* during the ripening process of pears; Fig.26 This is the color difference value Δb* diagram during the ripening process of pears; Fig. 27 The figure shows the weight loss rate, pulp hardness and brittleness of Zaosu pear after coating treatment with the change of storage days, among which, I is the weight loss rate with the change of storage days, II is the pulp hardness with the change of storage days, and III is the brittleness with the change of storage days; Fig.28 The figure shows the changes of TSS content, cell membrane permeability, respiration intensity and ethylene release of Zaosu pear with storage time, where I shows the changes of TSS content, cell membrane permeability, respiration intensity and ethylene release with storage time; II shows the changes of cell membrane permeability with storage time; III shows the changes of respiration intensity with storage time; IV shows the changes of ethylene release with storage time; Fig.29 The actual object and the size of the plaques are shown in the figure of the inhibitory effect of Zaosu pear film on Alternaria alternata after drying; Fig.30 This is a diagram of the preparation process and application model of dodecanedioic acid succinic anhydride starch nanocrystals. DETAILED DESCRIPTION The present invention is further described below in conjunction with specific embodiments.
[0021] Example 1: Figure 1-29As shown, a method for preparing dodecenyl succinic anhydride starch nanocrystals is as follows: after starch nanocrystals are prepared as a suspension, dodecenyl succinic anhydride (DDSA) ethanol solution is added to the starch nanocrystals to undergo an esterification reaction, and during the esterification reaction, atmospheric pressure plasma jet (APPJ) treatment is simultaneously performed. After the reaction is completed, centrifugation and washing are performed, and dodecenyl succinic anhydride starch nanocrystals are obtained after freeze-drying; the specific method is as follows: 1g of the prepared SNC is taken, 30 mL of 50% ethanol solution is added, and ultrasonic vibration is performed in a water bath for 30 minutes to obtain an SNC suspension. 1g DDSA is diluted to a 5mL volumetric flask with anhydrous ethanol to prepare a DDSA-ethanol solution with a concentration of 0.2g / mL. 400 μL of DDSA-ethanol solution was added dropwise to the SNC suspension, and the esterification reaction was carried out under stirring at 200 r / min at 35°C. The suspension was treated with APPJ within 24 minutes before the end of the reaction after the addition of DDSA-ethanol solution, wherein the APPJ treatment power was 300 w, the airflow was 20 mL / s, and the entire reaction time was 3 h. During the reaction, the pH of the reaction solution was adjusted with 0.1 mol / L NaOH to maintain the pH of the reaction solution between 8.5 and 9.5. After the reaction, the pH was adjusted to 6.8 with 0.1 mol / L HCl to terminate the reaction. The suspension was centrifuged and washed with 70% ethanol and anhydrous ethanol for 3 times, respectively, and freeze-dried for later use.
[0022] Example 2: A method for preparing an active film liquid using the DDSA-SNC prepared in Example 1, wherein the active film liquid is obtained by blending a Pickering emulsion stabilized by DDSA-SNC with a potato starch film-forming matrix.
[0023] The specific preparation method of the Pickering emulsion stabilized by DDSA-SNC is as follows: a thymol mixed solution (THY) is prepared using dodecenyl succinic acid starch nanocrystals as a stabilizer, and 5 mL of distilled water and 5 mL of thymol solution are mixed at room temperature at a speed of 10,000 rpm using a high-speed homogenizer (IKA T18 Ultra-Turrax, Staufen, Germany), and homogenized 3 times, each time for 1 min, wherein the mass ratio of thymol to anhydrous ethanol is 1:2. Before homogenization, 0.25 g of dodecenyl succinic acid starch nanocrystals are added to the thymol mixed solution THY, and the Pickering emulsion is prepared after homogenization.
[0024] The preparation method of potato starch film liquid (ps) is as follows: 100 g potato starch is mixed with 2 mL glycerol and 100 mL distilled water, and the mixture is placed in a water bath at 90°C for 30 min, and stirred continuously (200 r / min) until completely gelatinized, and then cooled for use.
[0025] 4% Pickering emulsion was added to the potato starch film liquid and stirred evenly to obtain the film-forming liquid.
[0026] Example 3: Application of the prepared active film liquid solution coated on the surface of fruits for preservation. Specifically, the Zaosu pears are immersed in 1.5% sodium hypochlorite for 1 minute for disinfection, and then rinsed with sterile water. The active film liquid solution is coated on the Zaosu pears to form an active film.
[0027] In order to illustrate the effect of the present invention, the following experimental verification is carried out: 1 Experimental methods 1.1 Preparation of starch nanocrystals Preparation method of potato starch nanocrystals (SNC): 250 g potato starch was mixed with 1000 mL sulfuric acid solution (3.16 M) and stirred at 40 ° C at a speed of 200 r / min for 7 days. After hydrolysis, centrifugation was performed and the solution was repeatedly washed with distilled water until the pH of the washing solution was 7, and SNC was obtained after freeze drying.
[0028] 1.2APPJ-assisted preparation of DDSA-SNC Take 1g of the prepared SNC, add 30 mL of 50% ethanol solution, and ultrasonically shake in a water bath for 30 minutes to obtain a SNC suspension. 1g of DDSA was diluted with anhydrous ethanol in a 5mL volumetric flask to prepare a DDSA-ethanol solution with a concentration of 0.2g / mL. 400μL of DDSA-ethanol solution was added dropwise to the SNC suspension, and stirred at 200r / min at 35℃. The 8% DDSA-SNC obtained by the reaction was marked as NT. APPJ was used to treat the DDSA-ethanol solution 0~24min before the end of the esterification reaction, and the 8% DDSA-SNC obtained was marked as E-24. The APPJ treatment power was 300w, the airflow was 20mL / s, the entire reaction time was 3h, and 0.1mol / L NaOH was used to adjust the pH throughout the process to maintain the pH between 8.5-9.5. After the reaction, 0.1mol / L HCl was used to adjust the pH to 6.8 to end the reaction. After the reaction, centrifuge and wash three times with 70% ethanol and anhydrous ethanol respectively, freeze-dry and set aside.
[0029] 1.3 Preparation of Pickering emulsion Thymol mixed solution (THY) was prepared using dodecenylsuccinate starch nanocrystals as a stabilizer. 5 mL of distilled water and 5 mL of thymol solution (the mass ratio of thymol to anhydrous ethanol was 1:2) were mixed by a high-speed homogenizer at room temperature at 10,000 rpm for 3 times, each time for 1 min to obtain the sample THY. Before homogenization, a certain amount of SNC, NT, and E-24 were added to the mixed solution to prepare the Pickering emulsions SNC / THY, NT / THY, and E-24 / THY.
[0030] 1.4 Preparation of composite film liquid The preparation method of potato starch film liquid (PS) is to mix 100g potato starch with 2mL glycerol and 100mL distilled water, and place in a water bath at 90℃ for 30min, and continuously stir (200r / min) until complete gelatinization, and then cool for use. 4% CE (coarse emulsion) and 4% PE are added to PS respectively and stirred evenly to obtain PS / CE and PS / PE film liquids respectively.
[0031] The preparation method of crude emulsion and Pickering emulsion is as follows: dodecenyl succinate starch nanocrystals are used as a stabilizer to prepare a thymol mixture, and 5 mL of distilled water and 5 mL of thymol solution (the mass ratio of thymol to anhydrous ethanol is 1:2) are mixed by using a high-speed homogenizer at room temperature at a speed of 10,000 rpm for 3 times, each time for 1 min. Before homogenization, 0.25 g of E-24 and 0.25 g of Tween are added to THY respectively, and PE (Pickering emulsion) and CE (crude emulsion) are prepared after homogenization and stored for later use.
[0032] 1.5 Application of fruit coating The Zaosu pears were immersed in 1.5% sodium hypochlorite for 1 minute for disinfection and then rinsed with sterile water. Three different film-forming solutions were prepared according to the method in 1.4 for coating Zaosu pear fruit. Then all Zaosu pears were randomly divided into three groups, namely PS, PS / CE and PS / PE. The pulp tissue of Zaosu pear fruit at the equator and 1 cm below the epidermis was taken on the 0th, 1st, 7th, 14th, 21st and 28th days of storage. The fruit tissue was added to liquid nitrogen and stored in a -80℃ refrigerator for further analysis of physiological indicators.
[0033] 2 Experimental results 2.1 DDSA-SNC Characteristics Analysis like Figure 1As shown in a, the particle size of the nanoparticles decreased after DDSA esterification. After APPJ treatment, the particle size was significantly reduced by 18.6%, and the particle size distribution gradually changed from 2 peaks to 1 peak. This shows that the large particles of DDSA-SNC were depolymerized after APPJ treatment, the volume was reduced, and the PDI was significantly reduced, and the effect of synergistic treatment was more obvious. This may be due to the high-energy substances generated during the plasma generation process bombarding the surface of SNC, causing the particle surface to etch or depolymerize. The potential of E-24 increased significantly by 24% compared with NT. This is mainly because the APPJ treatment broke the α-1,6 glycosidic bond, exposed more reaction sites, increased the degree of substitution of DDSA, and the negatively charged -COO - The increase of groups leads to a decrease in the negative potential of the particles. On the other hand, during the APPJ treatment, the oxygen in the air ionizes and oxidizes the DDSA-SNC particles, which reduces the potential. SNC and DDSA-SNC treated with different methods have similar FT-IR spectra. The characteristic peaks of the glucose unit of SNC include 2878 cm -1 stretching vibration at 1 650 cm -1 The stretching vibration of CO at 1248 cm -1 The CH bending vibration at 1545 and 1363 cm-1 of SNC substituted by DDSA remained basically unchanged under different treatments, indicating that the structure of the glucose unit is relatively stable and APPJ treatment will not destroy its structure. -1 New peaks gradually appear at 2930cm, which is caused by the stretching vibration of -COO- and C=C groups after the introduction of DDSA groups. The peak at 2930cm gradually increases, which is caused by the stretching vibration of -CH3 on the long fat link. The increase of the peak at 1545cm of E-24 indicates that DDSA-SNC has more -COO- groups, that is, APPJ treatment after the reaction has a better effect on increasing the degree of substitution than APPJ treatment before the reaction. The 3000-3600cm peak caused by -OH stretching vibration in the FTIR spectra of SNC and DDSA-SNC -1 The peaks at 928 cm-1 gradually became deeper and broader due to the APPJ treatment, which may be due to the introduction of -OH groups after the glycosidic bond -COC- was broken by the APPJ treatment. -1 This is also proved by the weakening of the -COC- stretching vibration peak. Therefore, APPJ treatment will lead to the cleavage of the -COC- glycosidic bond of the glucose unit and depolymerization of SNC. Compared with the APPJ pre-reaction treatment, the co-treatment of APPJ and DDSA can increase the number of glycosidic bond cleavages.
[0034] FTIR results show that APPJ treatment destroys the order of SNC, depolymerizes SNC, and exposes more substitution sites, which promotes the substitution reaction of DDSA. The characteristic peaks of H-NMR spectrum further quantify this result. Figure 2 As shown, the peaks at 5.5, 5.38, 4.57, 3.76-3.47ppm are characteristic peaks of OH2, OH3, OH1, H2-H6, respectively. The peak of the anomeric H proton on the α-1,4 glycosidic bond appears at 5.12ppm, which can be used as a reference for comparison with the integrated signal of the hydrophobic substituent. The methylene peak appears at 1.23ppm, which is offset from the result in 1.3.2 (1.02ppm). It may be due to the fact that the methylene fatty chains in the DDSA group are hydrophobic, and they may associate and aggregate in aqueous media, resulting in peak shifts. The peak at 0.85ppm is -CH3 on the long fatty chain of DDSA. It is determined by calculating the signal intensity ratio of the three protons on the terminal methyl group to the four protons on the anhydroglucose unit (AGU), the ratio of the proton intensity at the 0.86 ppm peak and between 4.5 and 5.5 ppm. The substitution degrees of NT and E-24 were 0.0208 and 0.0342, respectively. The substitution degree of E-24 was 32% higher than that of NT, and the substitution efficiency was increased by 26.7%. The substitution degree value measured by titration was basically consistent with the value obtained by NMR spectrum analysis. It may be that when DDSA esterification was performed after APPJ treatment, although more reaction sites were exposed after the glycosidic bond was broken, the further reaction was prevented due to the steric hindrance effect, so the substitution degree and substitution efficiency could not be improved; when DDSA esterification and APPJ synergistic treatment were performed at the end of the reaction, the system that had been in equilibrium continuously exposed more reaction sites, so that the remaining DDSA could continue to undergo esterification reaction, further improving the substitution degree and substitution efficiency. The peak at 4.60-4.62ppm is the characteristic peak of the anomeric hydrogen proton on the α-1,6 glycosidic bond. After APPJ treatment, the DB (branching degree) value decreased significantly from 7.229 to 5.330, indicating that APPJ treatment mainly destroys the α-1,6 glycosidic bond of SNC, breaks the -COC- bond, and causes the SNC branching degree to decrease and depolymerize, thereby increasing the -OH content and exposing more reaction sites, thereby improving the degree of substitution of DDSA-SNC. This result is consistent with the FTIR result.
[0035] Figure 3As shown in the figure, samples with different APPJ treatment times have obvious peaks at 2θ=17° and 22°, indicating that SNC still maintains a typical B-type crystal structure after APPJ treatment. However, APPJ treatment significantly reduces the relative crystallinity of DDSA-SNC, and the relative crystallinity of SNC-24min is reduced by 6.5% of SNC. The reduction in relative crystallinity is mainly due to the breakage of the crystal structure caused by APPJ treatment, while the crystalline region of SNC is mainly formed by the double helix structure formed by the aggregation of branched starch side chains connected by α-1,6 glycosidic bonds through hydrogen bonding, indicating that APPJ treatment breaks the α-1,6 glycosidic bonds in the crystalline region, destroys the double helix structure, thereby reducing the crystallinity and reducing the order of starch. This result is consistent with the results of FTIR and NMR. The RC value of SNC is no different from that of NT, indicating that when DDSA is esterified alone, it will not destroy the crystalline region of SNC, because the esterification of DDSA mainly occurs in the amorphous region. Therefore, the RC value of E-24 is significantly lower than that of SNC and NT, which indicates that when DDSA esterification and APPJ are treated simultaneously, there is a synergistic effect on the destruction of the SNC crystal region. After the energy input of APPJ treatment, the crystal region of SNC is damaged, which is conducive to the penetration of DDSA groups into the crystal region and forming ester bonds with SNC molecules, thus leading to the destruction of the crystal structure. The XRD reaction results are consistent with the FTIR and substitution results. The characteristic temperature of the DDSA-SNC endothermic transition at different APPJ treatment times is shown in Figure 2. Figure 4 As shown in the figure, all samples show an endothermic peak. The peak temperature and enthalpy value of E-24D were significantly reduced by 7°C and 8.13 J / g, respectively. This indicates that the DDSA esterification and APPJ co-treatment destroyed the crystals of SNC and reduced the double helix structure. This further illustrates that the depolymerization of SNC by APPJ occurs in the crystallization region, which is consistent with the XRD results; on the other hand, the value of ΔH often indicates the heat required to destroy the crystal structure of SNC, which is also related to the integrity of the crystal structure.
[0036] SEM results ( Figure 5 ) also observed the same results. With the increase of APPJ treatment time, obvious etching marks appeared on the surface of DDSA-SNC particles. In particular, due to the increase of DDSA substitution degree, the surface of E-24 particles became rough.
[0037] The particle size of NT increased after SNC esterification, which was mainly caused by the expansion of particles after grafting the characteristic structure of DDSA. After APPJ co-treatment, the particle size of E-24 decreased significantly compared with NT, and the particle size distribution changed from two peaks at 0 min to one peak, such as Figure 6-7As shown in the figure, it shows that the large particles of SNC are depolymerized after APPJ treatment, the volume is reduced, and the PDI is significantly reduced, and the effect of synergistic treatment is more obvious. The potential of E-24 is significantly increased by 24% compared with NT. This is mainly because the APPJ treatment breaks the α-1,6 glycosidic bond, exposes more reaction sites, increases the degree of substitution of DDSA, and increases the negatively charged -COO- groups on the particle surface, resulting in a decrease in the negative potential of the particles. On the other hand, during the APPJ treatment, the oxygen in the air ionizes and oxidizes the DDSA-SNC particles, which reduces the potential.
[0038] 2.2 Characteristics and stability of DDSA-SNC stabilized Pickering emulsion Different nanoparticles were added to a THY mixture (the volume ratio of THY alcohol solution to distilled water was 1:1) at a concentration of 10% (relative to the amount of THY added) to prepare an emulsion to stabilize the state of thymol and prevent its volatilization. SNC was unable to form a stable Pickering emulsion. When stored for 1 week, the emulsification index dropped significantly. At 4 weeks, no droplet morphology could be observed in the appearance and microscopic photos. This is because SNC itself only has a large number of -OH hydrophilic groups and does not have the conditions to form a stable O / W Pickering emulsion. According to the droplet size distribution of the emulsion, the distribution of the emulsion moved toward the direction of large particle size during the placement process, and the particle size of the E-24 / THY emulsion was the smallest during the entire process ( Figure 8 ), which is mainly due to the smaller particle size of E-24 compared to NT ( Fig. 9 ), more DDSA substituents, and higher absolute potential. Higher hydrophobic groups can improve the excessive hydrophilicity of SNC, which is more conducive to stabilizing the oil-water interface layer of Pickering emulsions, while smaller particle sizes can form smaller emulsion particle sizes, preventing emulsion aggregation and Ostwald ripening. The higher the absolute potential value of the particles, the higher the potential of the emulsion formed ( Fig.10 ), which can prevent the aggregation of emulsions. Therefore, after 4 weeks of storage, E-24 / THY can still maintain a low particle size and a high emulsification index, and the appearance of the emulsion still maintains a uniform emulsion layer ( Figure 11-12 ).
[0039] 2.3 Preparation of composite film liquid Optical microscopy results ( Figure 13-14) shows that the emulsion and its droplets in the coating liquid are approximately spherical. The droplet size of the PE emulsion is the smallest and has good dispersibility and stability. This result is consistent with the macroscopic photo results after 24 hours of placement (the emulsion is uniform and no stratification occurs). The particle size of CE is smaller than that of PE, but obvious stratification occurs after 12 hours of placement. This is because the absolute potential of CE is too low, and the emulsion droplets are easy to aggregate with each other, resulting in demulsification and stratification. The starch gelatinized liquid is uniform under the microscope. After adding the emulsions respectively, the emulsion droplets in ps / thy and ps / ce increase significantly, while the emulsion particle size in ps / pe remains basically unchanged. This is because when the emulsion is added to the starch film liquid, the absolute potential of THY and CE is too low, the emulsion droplets aggregate significantly and the particle size increases, while PE maintains a higher absolute point position. When added to the film liquid, the droplets repel each other, avoiding aggregation and maintaining the original particle size. The density of the oil phase is low, so the phenomenon of droplets agglomerating and floating on the membrane liquid surface is observed in the PS / CE macroscopic photograph, while no aggregation phenomenon is observed in the PS / PE macroscopic photograph.
[0040] The rheological property of the membrane liquid is an important parameter for the film-forming performance and uniformity of the thin film. Fig.15 The shear thinning behavior of starch film liquid can be observed, which is a typical characteristic of starch as a polymer after gelatinization. This is because the connection between starch molecules is destroyed faster than it is re-formed. When the emulsion is added to the starch film liquid, the viscosity of the film liquid is significantly reduced. This is mainly because the THY emulsion droplets block the cross-linking between the gelatinized starch molecules and reduce the contact area between the film liquid particles. In particular, PS / CE and PS / thy aggregate with each other after being added to the starch film liquid. Excessive THY lubricates the starch particles in the film liquid, accelerates fluidity, and reduces viscosity. However, at lower shear rates (<1s -1 ), the viscosity of PS / PE is higher than that of PS / CE. This is because the particle size of PE emulsion is small and the absolute potential is high, so that it still maintains a small particle size in the membrane liquid and is evenly dispersed in the starch gelatinization liquid, which weakens the destructive effect on the particle structure of the membrane liquid. Fig.16It shows that G` and G`` of all membrane liquids show frequency dependence, and both increase with the increase of angular frequency. The storage modulus of all samples is smaller than the loss modulus, indicating that the samples have liquid characteristics. The intersection point (COP) of G` and G`` appears at 7.94Hz for the Ps membrane, indicating that the deformation behavior dominated by viscosity changes to the deformation behavior dominated by elasticity. After adding PE, the COP of the membrane liquid increases to 15.849Hz, indicating that PE reduces the time required for starch polymer relaxation and disentanglement. This is because while the amphiphilic E-24 particle THY droplet surface forms a tight interface layer, its hydrophilic group (-OH) can interact with the hydroxyl group of starch gelatinized particles to form hydrogen bonds, enhance the interaction between the emulsion oil droplets and the starch particles, form a temporary network structure, and slow down the time for the starch membrane liquid to transform into an inelastic solid state.
[0041] The encapsulation rate of starch film liquid represents the degree of THY encapsulation of the active film after film formation. Figure 17-18 It can be concluded that with the increase of centrifugation time, the encapsulation rate gradually decreased, among which the encapsulation rate of PS / PE was significantly higher than that of PS / CE. This was mainly because THY was encapsulated by E-24 through Pickering emulsion, and the hydrophilic groups of E-24 interacted with starch granules and filled in the network structure of starch paste to form a new second external protective layer.
[0042] Molecular dynamics simulation is an effective tool for exploring molecular motion, which can make up for the shortcoming that conventional research methods are difficult to observe the diffusion of THY at the molecular scale. Based on the previous results, the two membrane liquids PS / CE and PS / PE were used as the research objects, and molecular dynamics simulation was used to analyze the interaction between the various components in the membrane liquid mixture at the molecular level. Fig.18 It directly reflects the diffusion of THY in the membrane liquid. In the ps / ce model, THY is dispersed in the membrane liquid medium before 10ns, aggregates after 20ns, and completely aggregates after 100ns. In the ps / pe model, during the 100ns process, THY is adsorbed together with E-24 nanoparticles and evenly dispersed in the membrane liquid system. No aggregation of THY occurs. This process is accompanied by E-24 tightly adsorbing THY while interacting with starch molecules and in close contact, thus maintaining the stability of the membrane liquid system and preventing the aggregation and diffusion of THY. The simulation results are consistent with the microscopic observations and encapsulation rate results, indicating that the simulation system has a high degree of credibility for studying the effects of real membrane liquid components. In order to better reflect the interaction forces between the various components in the membrane liquid, the Coulomb force and van der Waals force of each substance in the molecular simulation process are compared, such as Figure 19-22. As the simulation time increases, the van der Waals force between THY and starch gradually decreases, while the hydrogen bonding between THY remains unchanged. In the ps / ce model, the force between THY and the adsorbate remains unchanged, the force between the adsorbate and starch gradually decreases, while the hydrogen bonding between THY and starch and Tween remains unchanged, causing THY to aggregate. In the ps / ce model, the van der Waals force between THY and E-24 particles gradually increases and the hydrogen bonding effect strengthens, while the force between E-24 and starch remains unchanged. Therefore, THY and E-24 are tightly adsorbed and evenly dispersed in the membrane liquid during the entire simulation time, and no aggregation occurs. It can be seen that the adsorption between THY and starch and E-24 nanoparticles is mainly due to the interaction of van der Waals forces and hydrogen bonds. The diffusion coefficient (MSD) describes the dynamic characteristics of THY in the membrane liquid system. Fig.23 It can be seen that the addition of E-24 significantly reduced the MSD, indicating that E-24 effectively encapsulated THY and hindered the migration and diffusion of THY. Molecular dynamics simulation theoretically confirmed the diffusion effect of THY in the membrane solution.
[0043] 2.4 Film-coating preservation of Zaosu pear Fig.24 This is the change in the fruit skin of the Early Pear during storage. It can be seen that the coating treatment can delay the yellowing of the Early Pear skin during storage. PS-THY coating treatment will cause black spots to appear on the surface of the pear. This is mainly because THY cannot form a stable structure with the starch film-forming mechanism. During the drying process of the coating liquid, a large amount of THY migrates out of the film liquid matrix with water and comes into contact with the pear surface, causing damage, resulting in black spots on the pear surface. In contrast, PS-PE did not produce a similar damaging effect, also because the Pickering emulsion and the film matrix formed a very stable structure, and a large amount of it was preserved in the coating material. After the coating liquid dried, it could continue to come into contact with the pear in small amounts. The antioxidant property of THY can keep the pear green. Figure 25-26 It can be seen that the color difference values Δa* and Δb* gradually increase during the ripening process, but the color difference values after coating treatment are smaller than those of the control group. This shows that during storage, the skin of the Zaosu pear fruit turns slightly yellow, and the coating treatment can slow down the yellowing speed of the Zaosu pear. In particular, the green preservation effect of the PS-PE coating treatment is the best. This is consistent with Figure 4 The results of aⅠ are consistent.
[0044] Depend on Fig. 27It can be seen that the coating treatment can effectively reduce the weight loss of early crisp pears, especially the PS-PE coating treatment, the weight loss rate on the 7th day of storage is 50% of that of the PS-THY treatment. This is because in the PS-PE film-forming matrix, the THY Pickering emulsion is evenly dispersed in the starch gelatinized liquid, and interspersed with the free branched structure of starch to form a stable structure, thereby blocking or extending the penetration path of water molecules, further reducing the evaporation of water in the early crisp pears and reducing the weight loss rate. Fig. 27 Ⅱ In the experiment, as the ripening time prolonged, the flesh hardness showed a downward trend. On the 0th day, there was no significant difference in the flesh hardness of all groups, which indicated that the coating treatment could inhibit the decline of the flesh hardness of the fruit. Moreover, the PS-PE treatment could delay the softening of the early pear during the ripening process. On the 21st day, the hardness was 1.73 and 1.46 times that of the control group and the PS-THY treatment, respectively. Fig. 27 It can be seen from III that with the increase of storage days, the brittleness of Zaosu pear decreases, but the coating treatment has almost no effect on the brittleness of the pear.
[0045] During the ripening process, the TSS content of Zaosu pear fruit increases as the organic matter in the fruit is converted into soluble sugars, amino acids and vitamins. Fig.28 As shown in Figure 1, different coating treatments had no significant effect on the soluble solids content. However, during the 21-day storage process, the TSS treated with the PS-PE coating solution did not increase or decrease significantly. This may be because the PS-PE film solution matrix has good oxygen and water barrier properties, which reduces the respiration of the early pear, delays the ripening process of the fruit, and slows down the conversion and degradation of organic matter such as starch in the fruit. Cell membrane permeability is an important physiological indicator to measure the diffusion of cell contents to the outside of the cell, which can reflect the integrity of the cell membrane. Fig.28 As shown in Figure II, with the extension of storage time, the degree of cell senescence intensified and the cell membrane permeability increased. The cell membrane permeability of all treated early pears increased with the extension of storage time. The cell membrane permeability of early pears treated with PS-THY changed the most, increasing to 3.5 times that of the first day on the 21st day, while the cell membrane permeability of early pears treated with PS-PE was the lowest at 21 days. This may be due to the fact that the PS-THY coating caused phytotoxicity to the pears and accelerated the senescence of the fruit, while the thymol in PS-PE migrated slowly, and while the coating treatment reduced the respiration intensity, it also played an antioxidant role in the pears. During the ripening period, the respiration intensity of early pear fruit showed a downward trend, as shown in Figure 2. Fig.28III. The respiration intensity of the fruits in each treatment group was lower than that in the control group. This may be because the coating treatment thickened the epidermal protective layer and effectively closed the lenticels of the fruit epidermis, which not only prevented the transpiration of water, but also slowed down the gas exchange inside and outside the fruit, creating a controlled atmosphere, thereby inhibiting respiration. During the ripening process, the ethylene release of the early pear fruit showed a trend of first increasing and then decreasing. Fig.28 As shown in Figure IV, on the 1st, 7th, and 14th days, the ethylene content of PS-THY was higher than that of the control group, which may be due to the large amount of free thymol causing phytotoxicity to the early pear, resulting in the production of a large amount of ethylene. The ethylene produced by the PS-PE treatment was lower than that of the control group at all times, which may be due to the low-dose continuous release of thymol reducing the respiratory intensity, delaying the senescence of the fruit and the release of ethylene, or it may be due to the fact that thymol inhibited the activity of enzymes related to ethylene synthesis.
[0046] Fig.29 In the experiment, after the Zaosu pear film was dried, holes were punched at the equator and inoculated with a suspension of Alternaria alternata spores. The experimental results showed that the Zaosu pear film coated with PS-PE had a certain inhibitory effect on the inoculated Alternaria alternata. On the 15th day, the diameter of the Zaosu pear lesions treated with PS-PE was 61.3% smaller than that of CK. The results were the same as those of the in vitro antibacterial experiment. This shows that the PS-PE film effectively retains thymol and can continuously release it to achieve the purpose of long-term antibacterial.
[0047] 3. Conclusion DDSA esterification and APPJ synergistic treatment can increase the degree of substitution of DDSA on SNC, reduce the critical aggregation concentration of DDSA-SNC, and increase WCA. This is mainly due to the high-energy substances generated during the plasma generation process bombarding the surface of SNC, resulting in the cleavage of the glycosidic bonds in the molecular structure of the glucose unit, especially the COC of the α-1,6 glycosidic bonds, which leads to a decrease in the branching degree of SNC and depolymerization, thereby increasing the -OH content, exposing more reaction sites, and improving the degree of substitution and substitution efficiency of DDSA. SEM results show that etching marks appear on the surface of the particles after APPJ treatment, and the cleavage of the glycosidic bonds destroys the crystallization area, resulting in a decrease in the relative crystallinity of DDSA-SNC, and a decrease in the peak temperature and thermal enthalpy of DSC degradation. Large particles of DDSA-SNC are depolymerized after synergistic treatment, and the volume is reduced, resulting in a decrease in particle size and PDI. During the APPJ treatment, oxygen in the air ionizes and oxidizes the DDSA-SNC particles, reducing the potential. At the same time, after the degree of substitution increases, the negatively charged -COO- groups on the particle surface increase, which also leads to a decrease in the negative potential of the particles. This indicates that DDSA esterification and APPJ synergistic treatment can improve the degree of substitution of DDSA-SNC, solve the problem of low substitution efficiency of DDSA for SNC, and reduce the particle size and increase the absolute potential, making DDSA-SNC more suitable as a nanoparticle for stabilizing Pickering emulsions. This is a green and simple improvement method.
[0048] A feasible antioxidant and antibacterial coating was obtained by preparing Pickering emulsion using DDSA-SNC and mixing it in a starch-based film. The results showed that during the drying process of the active coating liquid PS-THY, thymol gradually migrated to the surface of the starch film as the water evaporated. However, in the PS-PE coating liquid, the Pickering emulsion and the free starch chains in the starch gelatinized liquid crossed each other and were embedded in the network structure of the starch film. The Pickering emulsion and the film matrix formed a stable structure, and most of the thymol was retained in the starch film after film formation. Due to the uniform distribution of thymol Pickering emulsion in the film-forming matrix, dense and uniform pores were formed in the dried starch film, making the film have the characteristics of sustained release. In addition, the application of the active coating liquid had a positive effect on the Zaosu pear, which was confirmed by the post-harvest physiological quality, such as Fig.30 As shown, including lower weight loss, higher hardness, lower respiration rate, etc. In summary, Pickering emulsion can be used as an effective method for active material carriers in the film preparation process.
[0049] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing dodecenylsuccinic anhydride starch nanocrystals, characterized in that: The method comprises the following steps: after starch nanocrystals are prepared into a suspension, an ethanol solution of dodecenylsuccinic anhydride (DDSA) is added to the suspension to undergo an esterification reaction, and during the esterification reaction, atmospheric pressure plasma jet (APPJ) treatment is simultaneously performed. After the reaction is completed, the suspension is centrifuged and washed, and then freeze-dried to obtain dodecenylsuccinic anhydride starch nanocrystals.
2. The method for preparing dodecenylsuccinic anhydride starch nanocrystals according to claim 1, characterized in that: The specific method is as follows: take 1g of the prepared SNC, add 30mL of 50% ethanol solution, and oscillate in a water bath for 30min to obtain a SNC suspension; add 1g of DDSA to a 5mL volumetric flask with anhydrous ethanol to make a DDSA-ethanol solution with a concentration of 0.2g / mL. 400 μL of DDSA-ethanol solution was added dropwise to the SNC suspension, and the mixture was stirred at 200 r / min at 35°C for esterification reaction. The 8% DDSA-SNC obtained by the esterification reaction was treated with APPJ before the addition of DDSA-ethanol solution and the reaction was completed. After the reaction, the mixture was centrifuged and washed three times with 70% ethanol and anhydrous ethanol, respectively, and freeze-dried for later use.
3. The method for preparing dodecenylsuccinic anhydride starch nanocrystals according to claim 2, characterized in that: DDSA was treated with APPJ during the esterification of SNC. The power was 300w, the airflow was 20mL / s, and the entire esterification reaction time was 3h, of which the APPJ treatment time was 24min.
4. The method for preparing dodecenylsuccinic anhydride starch nanocrystals according to claim 3, characterized in that: During the reaction, 0.1 mol / L NaOH was used to adjust the pH of the reaction solution to maintain the pH of the reaction solution between 8.5 and 9.
5. After the reaction, 0.1 mol / L HCl was used to adjust the pH to 6.8 to terminate the reaction.
5. The method for preparing dodecenylsuccinic anhydride starch nanocrystals according to claim 3, characterized in that: APPJ was used to treat the starch suspension 24 minutes before the end of the esterification reaction.
6. A method for preparing an active film liquid using the dodecenylsuccinic anhydride starch nanocrystals prepared according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: blending a DDSA-SNC stabilized Pickering emulsion with a potato starch film-forming matrix to obtain an active film liquid.
7. The method for preparing an active film liquid according to claim 6, characterized in that: The specific preparation method of the DDSA-SNC stabilized Pickering emulsion is as follows: a thymol mixed solution (THY) is prepared using dodecenylsuccinic acid starch nanocrystals as a stabilizer, 5 mL of distilled water and 5 mL of thymol solution are mixed at room temperature at a speed of 10,000 rpm using a high-speed homogenizer, and homogenized 3 times, each time for 1 min, wherein the mass ratio of thymol to anhydrous ethanol is 1:2, 0.25 g of dodecenylsuccinic acid starch nanocrystals are added to the thymol mixed solution THY before homogenization, and the Pickering emulsion is prepared after homogenization.
8. The method for preparing an active film liquid according to claim 7, characterized in that: The preparation method of potato starch film liquid (PS) is as follows: 100g potato starch is mixed with 2mL glycerol and 100mL distilled water, and the mixture is placed in a water bath at 90°C for 30min, and continuously stirred at 200r / min until completely gelatinized, and then cooled. Pickering emulsion is added to the potato starch film liquid and stirred evenly to obtain PS / PE film liquid.
9. The method for preparing an active film liquid according to claim 8, characterized in that: 4% Pickering emulsion was added to the potato starch film liquid and stirred evenly to obtain the film-forming liquid.
10. Use of the active film-forming liquid prepared according to any one of claims 6 to 9 for coating on the surface of fruits for preservation.
Citation Information
Cited By
Incense-burning oxygen-consuming carbon dioxide-supplementing food preservation bag for household refrigerator
CN224455047U